Community Action: A Strategy for Health Promotion - Hadi Tehrani; Mohammad Hosein Taghdisi (Iranian Association of Health Education and Health Promotion, 2015)
Community action is one of the health promotion strategies that is considered to solve health problems. Community action has a positive effect on the improvement of public health, especially in reducing non-communicable diseases. This strategy uses available resources within the community to implement changes. It is based on these principles: empowering communities to act effectively to improve health and empowerment of the health care system to work with communities. The purpose of strengthening community action is to support people to recognize their capacity for creating safe and healthy communities. Thus, community action is not imposed on individuals from special representative or specific organs.  Paper Type: Editorial